Global perspectives on the burden of chronic degenerative diseases in the elderly: a narrative review (Research, Society and Development, 2024)
This article explores the impact of chronic degenerative diseases in older people, with an emphasis on the need for integrated approaches to their management. The increase in life expectancy has led to a significant increase in these diseases, which are the main causes of disability and mortality among the elderly. Objective: to analyze global and regional trends in chronic degenerative diseases, highlighting risk factors and effective management strategies. The narrative review included an analysis of epidemiological and clinical studies published between 2019 and 2023, using databases such as PubMed and Scopus. The selection of articles was based on inclusion criteria that considered studies of high scientific relevance. Chronic degenerative diseases, such as osteoarthritis, rheumatoid arthritis and neurodegenerative diseases, have a significant impact on the quality of life of the elderly, affecting both physical health and emotional and social aspects. Factors such as genetic predisposition, inadequate lifestyle and environmental conditions were identified as the main risks. An integrated approach, which combines clinical efforts and health policies, is essential to mitigate the effects of these diseases in the elderly, ensuring healthy and active aging. Continued research and development of new therapies are critical to optimizing the management of these complex conditions.